2003
DOI: 10.1901/jaba.2003.36-297
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Presession Attention on Problem Behavior Maintained by Different Reinforcers

Abstract: The effect of presession attention on the later occurrence of problem behavior was examined with elementary-school children with a range of disabilities. Results of analogue functional analyses suggested an escape function, an attention function, or both. Following the analogue functional analyses, the effects of two antecedent conditions (10-min ignore vs. 10-min attention) were compared on problem behavior in subsequent test conditions. For participants who displayed attention-maintained problem behavior, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 8 publications
2
33
0
2
Order By: Relevance
“…First, EOs can influence the power of consequences to act as reinforcers. For example, when a person is deprived of attention then attention might act as a more powerful reinforcer (McComas, Thompson, & Johnson, 2003). This is termed the reinforcer-establishing effect.…”
Section: Introductionmentioning
confidence: 99%
“…First, EOs can influence the power of consequences to act as reinforcers. For example, when a person is deprived of attention then attention might act as a more powerful reinforcer (McComas, Thompson, & Johnson, 2003). This is termed the reinforcer-establishing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that prior access to social sources of reinforcement (e.g., attention) may alter the subsequent value of that stimulus event as reinforcement for appropriate behavior (Vollmer & Iwata, 1991;Zhou, Iwata, & Shore, 2002) and problem behavior (McComas, Thompson, & Johnson, 2003). Given these results, it is possible that the stimulation generated by stereotypy may be less efficacious following a period of time when prior access to that stimulation was available (as evidenced by decreased levels of behavior).…”
Section: Introductionmentioning
confidence: 99%
“…In marked contrast, changes in the level of attention did not appear to function as MOs for escape-maintained behavior (e.g., McComas et al, 2003). Although the effects were somewhat mixed, providing access to different types of tangible reinforcement did appear to have an abolishing effect on some participants' escape-maintained behavior (e.g., Carter & Wheeler, 2007).…”
Section: Establishing or Abolishing Operationmentioning
confidence: 93%